2023
DOI: 10.3171/case23118
|View full text |Cite
|
Sign up to set email alerts
|

Selective transarterial embolization for arterial hemorrhage after upper third molar extraction: illustrative cases

Abstract: BACKGROUND The present report describes 2 cases of arterial bleeding after removal of the upper third molar that were successfully treated with selective transarterial embolization. OBSERVATIONS The first patient underwent removal of the left upper third molar. A few hours later, facial swelling and massive bleeding appeared near the extraction socket involving the posterolateral wall of the maxillary sinus. Angiography showed a pseudoaneurysm involving the posterior superior dental artery, and the lesion wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…With regards to the management of postoperative hemorrhagic complications, some authors used selective transarterial embolization in order to treat the emergence after third molar extraction or to enhance coagulation after venous mandibular neoformation surgery [ 26 , 27 , 28 , 29 ]. Gogulanathan et al [ 30 ] in their interesting randomized slit-mouth clinical trial reported superior results after third molar extraction in the group with fibrin sealant compared to traditional suture, with superior values of postoperative wound closure and mouth opening and reduced values in duration to achieve hemostasis and pain score.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to the management of postoperative hemorrhagic complications, some authors used selective transarterial embolization in order to treat the emergence after third molar extraction or to enhance coagulation after venous mandibular neoformation surgery [ 26 , 27 , 28 , 29 ]. Gogulanathan et al [ 30 ] in their interesting randomized slit-mouth clinical trial reported superior results after third molar extraction in the group with fibrin sealant compared to traditional suture, with superior values of postoperative wound closure and mouth opening and reduced values in duration to achieve hemostasis and pain score.…”
Section: Discussionmentioning
confidence: 99%